Detrimental Effects of HMGB-1 Require Microglial-Astroglial Interaction: Implications for the Status Epilepticus -Induced Neuroinflammation - Rosciszewski, Gerardo; Cadena, Vanesa; Auzmendi, Jerónimo; Cieri, María Belén; Lukin, Jerónimo; Rossi, Alicia R.; Murta, Veronica; Villarreal, Alejandro; Reinés, Analia; Gomes, Flávia C. A.; Ramos, Alberto Javier (Frontiers in Cellular Neuroscience, 2019)
Temporal Lobe Epilepsy (TLE) is the most common form of human epilepsy and available treatments with antiepileptic drugs are not disease-modifying therapies. The neuroinflammation, neuronal death and exacerbated plasticity that occur during the silent period, following the initial precipitating event (IPE), seem to be crucial for epileptogenesis. Damage Associated Molecular Patterns (DAMP) such as HMGB-1, are released early during this period concomitantly with a phenomenon of reactive gliosis and neurodegeneration. Here, using a combination of primary neuronal and glial cell cultures, we show that exposure to HMGB-1 induces dendrite loss and neurodegeneration in a glial-dependent manner. In glial cells, loss of function studies showed that HMGB-1 exposure induces NF-kB activation by engaging a signaling pathway that involves TLR2, TLR4 and RAGE. In the absence of glial cells, HMGB-1 failed to induce neurodegeneration of primary cultured cortical neurons. Moreover, purified astrocytes were unable to fully respond to HMGB-1 with NF-kB activation and required microglial cooperation. In agreement, in vivo HMGB-1 blockage with glycyrrhizin, immediately after pilocarpine-induced status epilepticus, reduced neuronal degeneration, reactive astrogliosis and microgliosis in the long term. We conclude that microglial-astroglial cooperation is required for astrocytes to respond to HMGB-1 and to induce neurodegeneration. Disruption of this HMGB-1 mediated signaling pathway shows beneficial effects by reducing neuroinflammation and neurodegeneration after status epilepticus. Thus, early treatment strategies during the latency period aimed at blocking downstream signaling pathways activated by HMGB-1 are likely to have a significant effect in the neuroinflammation and neurodegeneration that are proposed as key factors in epileptogenesis.